Nghiên cứu phản ứng khâu mạch quang của dầu hạt cây đen acrylat hóa - Hiền, Lê Xuân; Thắng, Đàm Xuân; Việt Triều, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The photocrosslinking of the coatings on the base of acrylated black seed oil (ABSO) in presence of the radical photoinitiator I.184 have been studied. It was shown that under UV–exposure, the acrylate groups were converted rapidly and reached the final conversion in the range of 95 % to 99 %, depending on the acrylation degree of the oil and nature of the acrylate group: The higher the acrylation degree, the faster the conversion. Acrylate groups were more reactive than methacrylate groups in the reaction. It was indicated also that the gel fraction, swelling degree and relative hardness of the photocrosslinked coatings were changed in concomitance with the conversion of acrylate groups. Among the coatings investigated the one on the base of ABSO having 2.0 mol acrylate/mol oil showed the best gel fraction 74 %, swelling degree 245 % and relative hardness 0.36. Keywords: Black seed oil, acrylated vegetable oil, photocrosslinking